Barriers and outcomes of therapeutic communication between nurses and patients in Africa: a scoping review - Susanna Aba Abraham; Frederick Nsatimba; Dorcas Frempomaa Agyare; Joyce Agyeiwaa; Rita Opoku-Danso; Jerry Paul Ninnoni; Patience Fakornam Doe; Benjamin Osei Kuffour; Benjamin Kofi Anumel; Gifty Osei Berchie; Christian Makafui Boso; Andrews Agyei Druye; et al. (BMC, 2024)
Abstract Background Therapeutic communication (TC) promotes effective patient care, emotional wellbeing, and improves patient outcomes. The purpose of this review was to synthesise evidence on barriers and outcomes of TC between nurses and patients in Africa and to inform future studies and systematic reviews. Methods Search for the records was done in four major databases including PubMed, Science Direct, PubMed CENTRAL, and JSTOR. Additional searches were done in Google Scholar and Google. Results and findings from published studies and grey literature were included. A total of 16 articles met the eligibility criteria and were included in the review. This scoping review followed the guidelines by Askey and O'Malley. Results Barriers associated with TC were grouped under five main themes: sociodemographic factors, patient-related factors, nurse-related factors, environmental and health service-related. Age, and religious beliefs were the main sociodemographic factors that hindered TC while stress and inadequate knowledge and skills were identified among the nurse-related barriers to TC. Extreme weather conditions and mosquito infestation were environmental factors while lack of access to TC educational programmes on TC was a health service-related factor that interfered with TC. Both positive and negative outcomes of TC were also identified. Conclusion Continuous professional development on TC is necessary to improve nurses' attitudes and update their skills to enable them to render culturally competent nursing care to patients.